2022
DOI: 10.1111/bjd.20654
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of gene–gene interaction in hidradenitis suppurativa: a nationwide registry study of Danish twins

Abstract: Summary Background Hidradenitis suppurativa (HS) is a recurrent inflammatory skin disease that, apart from rare causative loss‐of‐function mutations, has a widely unknown genetic aetiology. Objectives To estimate the relative importance of genetic and environmental factors underlying susceptibility to HS. Methods Via the Danish Twin Registry and the Danish National Patient Registry we pulled together information on zygosity with that of HS status. Cases of HS were identified by the International Classification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
25
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 48 publications
1
25
0
1
Order By: Relevance
“…In this issue of the BJD , the study by Kjærsgaard Andersen et al . cross‐references Danish National Twin Registry data with International Classification of Diseases 8/10 codes for HS to provide a robust heritability estimate for HS of 80% [95% confidence interval (CI) 67–93] 1 . This estimate is in line with a previous twin study, which identified a heritability for HS of 77% (95% CI 54–90), despite using different methodologies 2 …”
supporting
confidence: 78%
See 2 more Smart Citations
“…In this issue of the BJD , the study by Kjærsgaard Andersen et al . cross‐references Danish National Twin Registry data with International Classification of Diseases 8/10 codes for HS to provide a robust heritability estimate for HS of 80% [95% confidence interval (CI) 67–93] 1 . This estimate is in line with a previous twin study, which identified a heritability for HS of 77% (95% CI 54–90), despite using different methodologies 2 …”
supporting
confidence: 78%
“…also allows for nongenetic (e.g. environmental) contributions to HS 1,8 . Distinct HS phenotypes each seem to be associated with different environmental factors such as smoking or obesity, suggesting an important role for gene–environment (G × E) interactions 8 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the high heritability estimates of HS (77–80%) only a minority of HS patients demonstrate a strong monogenic etiology in the context of familial or syndromic HS (5%) ( Kjaersgaard Andersen et al, 2021 ). Nevertheless, common forms of the disease demonstrate familial segregation.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, information on remission rate for this group may be of higher interest to physicians treating patients with HS. The prevalence of the subgroup with self‐reported HS from ≥3 areas was 0.3%, a figure that reflects both the cumulative incidence of diagnosed HS patients amongst Danish twins by age 40 years (female: 0.35%, male: 0.13%), 24 and the 0.19% prevalence found in a Danish nation‐wide register study on physician diagnosed HS 5 . Ultimately, this indicates that the ≥3 areas subgroup is similar to patients diagnosed with HS by a physician.…”
Section: Methodsmentioning
confidence: 95%